増大傾向を示した舌下腺による静止性骨空洞の長期観察例 - 安居, 孝純; 軽部, 健史; 鬼澤, 勝弘; 河奈, 裕正; 莇生田, 整治; 佐藤, 仁 (日本口腔外科学会雑誌, 2016)
Lingual bone defects are usually asymptomatic local concavities of the lingual cortical bone of the mandible, frequently caused by soft-tissue inclusion. In most cases, the soft tissue is the submandibular gland. Only 7 cases of developing lingual bone defects were previously reported in Japan, but none of these cases involved the sublingual gland. We report a rare case of a developing lingual bone defect associated with the sublingual gland, which we followed up for 21 years. The patient was a 58-year-old man who had a developing lingual bone defect in the anterior right side of the mandible. A panoramic X-ray film showed an oval radiolucent area in the apical region of the lower right canine and first premolar tooth. Moreover, electric pulp testing confirmed that all teeth in the lower-right quadrant were vital. A panoramic X-ray film obtained at a nearby dental clinic demonstrated a radiolucent area 15 years before presentation to our department, and the area showed evidence of gradual expansion. Computed tomography revealed a local concavity in the lingual cortical bone of the right side of the mandible. The concavity measured 13 × 9 mm. The signal intensity of the inner tissue of the bone defect was nearly equivalent to that of the sublingual gland on T1-, T2-weighted magnetic resonance imaging. The suspected clinical diagnosis was a lingual bone defect. We performed an incisional biopsy to rule out a neoplastic lesion, and the histopathological diagnosis was normal sublingual gland tissue. On the basis of these results, the final diagnosis was a developing lingual bone defect associated with the sublingual gland. Two years have elapsed, but there is no swelling or induration in the right sublingual gland. The radiolucent area on the panoramic X-ray film showed decreased radiolucency and increased bone volume. Moreover, computed tomography revealed that the concavity of the bone had shrunk.